PENGARUH PEMASARAN WORD OF MOUTH DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI COFFEE SHOP SIMALIS - Kusumaningtyas, Fiyar Nur Hafizhah; Saputra, Eryd (Puslitabmas Batam Tourism Polytecnic, 2023)
This study aims to determine the influence of word of mouth and brand trust on consumers' purchasing decisions at Simalis coffee shop. This type of research is quantitative. The population in this study was 500 simalis coffee shop consumers using the slovin formula technique, so the sample needed was 222 respondents. The data collection techniques used in this study were questionnaires, and interviews. This study uses Validity Test tools, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Partial Test, Simultaneous Test and Coefficient of Determination Test. The results of this study show that word of mouth affects consumers' purchasing decisions, brand trust affects consumers' purchasing decisions, and word of mouth and brand trust affect consumers' purchasing decisions simultaneously at simalis coffee shop